As imagens multifacetadas da palavra: a literatura na escola. - Darolt, Carolina Amália Witzke (2004)
This research work is a Case Survey, accomplished in Escola Sarapiquá (Sarapiquá School), located in the city of Florianópolis, in Santa Catarina State. The school emerged from the concern of a group of parents about the education of their children. Interested in offering these children a different education from the one established in the city of Florianópolis, these parents launched the school works on December 1st , 1981, when the first assembly took place in the Health Sciences Center of the University of Santa Catarina State. The schoolassociation was officially established on February 10th, 1982 and became the Cultural Association Rising Sun (Associação Cultural Sol Nascente), and finally given the informal name of Escola Sarapiquá. The aim of the research was to give visibility to the cultural-scientific net of meanings, built by the literary within the school. This way, searching for a direct meeting with the subject, were used as a tool of research, the following: the analysis of documents of the school; the reading of works accomplished by students of the 5th grade of elementary education; observation of the school´s routine, and the achievement of interviews with teachers and students. The data built together with the subjects of the research were analyzed, starting from the indicative paradigm of Ginzburg, the listening of deaf clues, the attention to the unsaid, raised through sense of smell and intuition; Maturana and Varela and the work with reason and emotion; Morin, through the order/disorder concept and the work with uncertainties, among others. The results show that literature takes a place of distinction within the school´s routine which transcends the Portuguese Language classes. The literature language is part of many moments of the school and involves different people, taking shape as a non-disciplinary knowledge.